Influencing factors of quality of life among front-line nurses who collected nucleic acid samples during COVID-19: a path analysis - Yan, Jiaran; Wu, Chao; Liu, Yu; Zhang, Hongli; He, Chunyan; Lin, Yawei; Li, Yang; Zhang, Yuhai; Li, Yinglan; Lang, Hongjuan (Frontiers in Public Health, 2023)
Aim: To investigate the quality of life of nurses who collected nucleic acid samples throughout the COVID-19 epidemic's routine management, as well as the factors that may have influenced it. Background: After the outbreak of the COVID-19, normalized epidemic prevention and control throughout China implemented. Nucleic acid testing has become an effective measure for the early detection of virus-infected individuals. Nurses collecting nucleic acid samples undertake important tasks. Their quality of life is significant to maintaining team stability and containing the epidemic. However, research on their quality of life is still limited. Methods: A cross-sectional survey was conducted on 1, 292 nurses who collected nucleic acid samples from five tertiary general hospitals in Xi'an through self-reported electronic questionnaires (including general demographic information, the Connor-Davidson Resilience Scale, the Social Support Rating Scale, and the World Health Organization Quality of Life Brief Scale). Descriptive, one-way ANOVA, and multiple linear regression were performed using SPSS 26.0. Structural equation modeling was used to analyze the influencing factors. Results: The nurses collecting nucleic acid samples had a modest level of quality of life. Age, marital status, average daily sleep duration, frequency of exercise, psychological resilience, and social support were all factors in the regression equation of quality of life, according to multiple linear regression analysis. Quality of life was significantly positively correlated with psychological resilience and social support. Conclusions: Demographic characteristics, psychological resilience, and social support are the factors affecting the quality of life of nurses who collect nucleic acid samples. Nursing managers should focus more on these factors to improve the quality of life for nurses. Relevance to clinical practice: Nursing managers should realize the importance of the quality of life of nurses who collect nucleic acid samples in maintaining a vigorous nursing team and ensuring an optimized epidemic control. Social support should also be provided to nurses to improve their psychological resilience, thereby improving nurses' quality of life.